2009
DOI: 10.3163/1536-5050.97.1.006
|View full text |Cite
|
Sign up to set email alerts
|

The Mobile Reference Service: a case study of an onsite reference service program at the school of public health

Abstract: The School of Public Health at Saint Louis University is located at a greater distance from the library than other programs on the main medical center campus. Physical distance diminishes the ease of access to direct reference services for public health users. To bridge the gap, the library developed the Mobile Reference Service to deliver on-site information assistance with regular office hours each week. Between September 2006 and April 2007, a total of 57 in-depth reference transactions took place over 25 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
(15 reference statements)
0
13
0
Order By: Relevance
“…Kesselman and Watstein (2009) (Covone & Lamm, 2010;Matava, Coffey, & Kushkowski, 2010;Matos, Matsuoka-Motley, & Mayer, 2010), to more than 50 percent of time spent in the customer's environment (Bartnik, 2007;Brown & Leith, 2007;Fitzgerald, Anderson, & Kula, 2010;Freiburger & Kramer, 2009;Martin, 2010). In the past, similar initiatives have been referred to as mobile or onsite reference, not embedded librarianship (Lee, Hayden, & MacMillan, 2004;Tao, McCarthy, Krieger, & Webb, 2009). …”
Section: History and Definitionsmentioning
confidence: 99%
“…Kesselman and Watstein (2009) (Covone & Lamm, 2010;Matava, Coffey, & Kushkowski, 2010;Matos, Matsuoka-Motley, & Mayer, 2010), to more than 50 percent of time spent in the customer's environment (Bartnik, 2007;Brown & Leith, 2007;Fitzgerald, Anderson, & Kula, 2010;Freiburger & Kramer, 2009;Martin, 2010). In the past, similar initiatives have been referred to as mobile or onsite reference, not embedded librarianship (Lee, Hayden, & MacMillan, 2004;Tao, McCarthy, Krieger, & Webb, 2009). …”
Section: History and Definitionsmentioning
confidence: 99%
“…For example, a 2009 case study completed at St. Louis University in Missouri found that the use of mobile reference services coincided with a reduced use of face-to-face information assistance (Tao, McCarthy, Krieger, & Webb, 2009). However, results from the same study show an increased use of library resources as a whole, especially electronic resources.…”
Section: Medical Librarianship As a Case Studymentioning
confidence: 99%
“…However, results from the same study show an increased use of library resources as a whole, especially electronic resources. Between September 2006 and April 2007, the total reference inquiries received from public health usersincluding those from the Mobile Reference Service-increased by 28% (to 146 from 114) (Tao et al, 2009).…”
Section: Medical Librarianship As a Case Studymentioning
confidence: 99%
“…Haines' efforts at the University of Michigan led to her being invited to serve on the school's staff retreat planning committee and to social gatherings (2004). Tao, McCarthy, Krieger, and Webb (2009) report an increase in reference transactions, use of electronic course reserves, liaison contacts and understanding of the users, programs and activities of the school in which they were providing services. They met their objectives of strengthening liaison relationships, and improving library support for research and scholarship.…”
Section: Literature Reviewmentioning
confidence: 99%